Clinicopathological analysis of ovarian tumours: experience of 3 years in a cancer hospital - Varsha Deshmukh; Afsha Suboohi (Barpeta Obstetrics and Gynaecological Society, 2022)
Objective: The objective of this study was to study the distribution of ovarian tumors histopathologically in different age groups and their various clinical presentations. Methods: 100 patients who presented with 142 ovarian lesions on either or both sides were analyzed during a period of 3 years and a further two year follow-up of patients with malignant tumors were done in a tertiary cancer hospital. Results: There were 142 lesions comprising of 56% of neoplastic lesions, 30% of non-neoplastic lesions and 14% borderline lesions. Serous tumors were the commonest tumors (42%) followed by germ cell tumors. Serous cystadenoma (33.3%) was the commonest non-neoplastic lesion. The distribution of benign tumors in the reproductive age groups was more commonly seen. Malignant tumors were in the perimenopausal and postmenopausal age group (57.1%). Bilaterality of lesions was seen in 42 patients. Lump in abdomen was seen in 62.5% cases with benign lesions and vague discomfort was reported in all cases of malignant ovarian tumors. Out of 56 cases of malignant ovarian tumor, 34 patients presented in stage 1 and 10 patients presented in stage 4. Conclusions: Ovarian neoplasia is one of the most common and lethal malignancy in female reproductive tract in older age group. Since most of the ovarian cancer remain asymptomatic for prolong period so measures should be taken for early diagnosis for better outcome.